Contemporary Russian political drama vis-à-vis tradition and continuity - Olaszek, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
Eminent Russian theatre makers, playwrights and theatre critics are not unanimous in their opinion on the matter of the indispensability of political drama. The majority of them maintain that there is a need for political drama in the times of excessive politicization of the mass media. However, they make it clear that theatre productions should not be a direct response to the events, actions and political activities of the governing authorities, individuals and organizations, but merely reflections on the human condition in the new social reality. The subject of our study is the issue of references in the recent Russian political drama to the the politicized Soviet plays of the 1970 with respect to the theme: an individual vs. government, the principles of exercising power, democracy and equal rights and the role of the mass media; and with respect to artistic means of expression: narrative and journalistic, a documentary and parodic manner, the poetics of the absurd and non-canonical genre stylization. From the point of view of the theme, the contemporary drama continues the tradition of the leading playwrights of the ‘new wave’, and as for the way of expression, new solutions are proposed, such as: irony, parody, and the idea of the absurd, with reference to theatre of the absurd.